Performance Evaluation of the FCI-DAB as a Single-Stage and Storage Capacitorless PFC Wireless Charger - Itziar Alzuguren; Asier Garcia-Bediaga; Ander Avila; Alejandro Rujas; Miroslav Vasic (IEEE Access)
This paper compares two single-stage (1-S) topologies for Electric Vehicle (EV) wireless battery chargers. The Single Stage Resonant-Dual Active Bridge (SSR-DAB) topology is a very compact topology due to the lack of input and output interfaces, reducing considerably the passive components of the circuit. However, its main disadvantage compared to two-stage (2-S) solutions is the fact that it transmits the low frequency fluctuation to the output, which is solved with the recently presented Floating Capacitor Integrated-Dual Active Bridge (FCI-DAB) topology, thanks to the active filter connected in series on the primary-side of the converter. The topologies are compared in terms of controllability, bifurcation, grid current quality and system power losses, taking into account two different control strategies: duty-cycle control on the primary-side and duty-cycle control on the secondary-side of the circuit. The study concludes that the FCI-DAB works better dealing with bifurcation and grid current distortion, while the SSR-DAB converter is not able to guarantee full performance with a single control strategy. The study is validated by experimental results obtained from a scaled down GaN-based Inductive Power Transfer (IPT) 1.5 kW battery charger, achieving 93 % of efficiency and PF=0.99.